The Use of the Data Envelopment Analysis (DEA) Method in Measuring the Efficiency of Sharia Rural Banks (BPRS) in D.I. Yogyakarta - Muallimah, Lilis; Haq, Furqonul (Journal of Islamic Economic Scholar, 2024)
This research aims to analyze the level of efficiency in the financial performance of the Sharia People's Financing Bank of D.I. Yogyakarta during the period from 2014 to 2023. The data source for this research is secondary data obtained from the annual reports of each Sharia People's Financing Bank, with a sample of 11 banks using the purposive sampling method. this research uses the Data Envelopment Analysis (DEA) method with the DEAP 2.1 software. The input variables in this study are total assets, third-party funds, and operational costs, while the output variables in this study are financing and income. The research results show that during the period 2014-2023, out of 11 Sharia People's Financing Banks, 9 Sharia People's Financing Banks achieved a perfect efficiency score of 100% or 1, and 3 Sharia People's Financing Banks have not yet achieved a perfect efficiency score of 100% or 1.